225 intracranial aneurysms treated with the Low-profile Visualized Intraluminal Support (LVIS) stent: a single-center retrospective study. (3rd June 2018) - Su, Wei; Zhang, Yisen; Chen, Junfan; Liu, Jian; Rajah, Gary; Yang, Xinjian
Abstract: Background For the treatment of intracranial aneurysms, the low-profile visualized intraluminal support (LVIS) stent is a new generation of highly visible-braided stent that was recently introduced in China. Here, we report our single-center retrospective experience of safety and efficacy utilizing LVIS for stent-assisted coiling of intracranial aneurysms. Methods We included 218 patients with intracranial aneurysms consecutively treated with LVIS SR stents at our center in this study. Postoperative and follow-up embolization scores, procedural complications, clinical and angiographic findings at mid-term follow-up, as well as recurrence rate, preoperative and follow-up mRS scores were analyzed. Results Two hundred and eighteen patients with two hundred and twenty five intracranial aneurysms were enrolled. The locations and distribution were ICA (125, 55.6%), PcomA (47, 20.9%), VA (38, 16.8%), and BA (15, 6.7%). Two hundred and eighteen aneurysms were treated with the stent-assisted coiling and seven patients with LVIS stents alone. Angiographic follow-up was available for 115 (51.1%) aneurysms, 8 (7.0%) of which had recurrences including 7 (6.5%) unruptured aneurysms and 1(14.3%) ruptured aneurysm. The procedural complication rate was 2.75% in total, including distal hemorrhage (1, 0.45%; SAH), ischemic events (5, 2.3%). Conclusions Our single-center retrospective experience is one of the larger studies to date assessing the LVIS device. Compared with many laser-cut stent studies, the LVIS device had a higher aneurysm complete occlusion rate at follow-up coupled with low complication rates. However, this study was our initial experience with LVIS, larger patient numbers, and longer follow-up will be needed to fully assess the long-term efficacy of LVIS in treating intracranial aneurysms.